Analysis of somatic molecular changes, clinicopathological features, family history, and germline mutations in colorectal cancer families: evidence for efficient diagnosis of HNPCC and for the existence of distinct groups of non-HNPCC families. Issue 10 (23rd March 2005) - Johnson, V; Lipton, L R; Cummings, C; Eftekhar Sadat, A T; Izatt, L; Hodgson, S V; Talbot, I C; Thomas, H J W; Silver, A J R; Tomlinson, I P M
Abstract : Objective: To analyse somatic molecular changes, clinicopathological features, family history, and germline mutations in families with colorectal cancer (CRC). Methods: Molecular changes (K-ras and β-catenin mutations, chromosome 18q allele loss (LOH), APC LOH, microsatellite instability (MSI), and expression of β-catenin and p53) were examined in four series of CRC patients with proven or probable hereditary disease: hereditary non-polyposis colon cancer (HNPCC); MYH associated polyposis (MAP); multiple (>5) colorectal adenomas without familial adenomatous polyposis (FAP); and other families/cases referred to family cancer clinics (FCC series). HNPCC was diagnosed using a combination of germline mutation screening and tumour studies. A series of unselected CRC patients was also studied. Results: There was overlap between genetic pathways followed by each type of CRC, but significant differences included: increased frequency of K-ras mutation and reduced frequency of APC LOH in cancers from MAP, but not from multiple adenoma patients; reduced frequency of LOH in HNPCC CRCs; and increased MSI in CRCs from HNPCC, but not from FCC or multiple adenoma patients. HNPCC was apparently detected efficiently by combined germline and somatic analysis. Cancers from the FCC, unselected, and multiple adenoma series shared similar molecular characteristics. In the FCC and multiple adenoma series, hierarchical cluster analysis using the molecular features of the cancers consistently identified two distinct groups, distinguished by presence or absence of K-ras mutation. Conclusions: While K-ras mutation status is known to differentiate hereditary bowel cancer syndromes such as MAP and FAP, it may also distinguish groups of non-HNPCC, FCC patients whose disease has different, as yet unknown, genetic origins.